2020
DOI: 10.1155/2020/4242989
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentric, Retrospective Efficacy and Safety Study of Nanosomal Docetaxel Lipid Suspension in Metastatic Castration-Resistant Prostate Cancer

Abstract: Purpose. To evaluate the efficacy and safety of nanosomal docetaxel lipid suspension (NDLS, DoceAqualip) in patients with metastatic castration-resistant prostate cancer (mCRPC). Materials and Methods. In this multicenter, retrospective study, we analyzed the medical charts of mCRPC patients, who were treated with NDLS administered as 2-weekly (50 mg/m2) or 3-weekly regimens (75 mg/m2). The study endpoints were prostate-specific antigen (PSA) response (>50% PSA decline from baseline), PSA progression (PSA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a previous study PSA responses were reported in 77.8% vs. 60% patients receiving biweekly (N ¼ 9) and once every 3 weeks (N ¼ 15) NDLS, respectively. 23 The most common AEs with biweekly docetaxel in PROSTY were fatigue (89%), anemia (86%), pain (70%), neutropenia (60%), watery eyes (53%) and raised alkaline phosphatase concentration (50%); most common grade 3/4 AEs included neutropenia (36%), fatigue (15%), leucopenia (13%), infection (11%), and infection with neutropenia (6%). In our case series, anemia, lymphopenia, and neutropenia were the most common AEs.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study PSA responses were reported in 77.8% vs. 60% patients receiving biweekly (N ¼ 9) and once every 3 weeks (N ¼ 15) NDLS, respectively. 23 The most common AEs with biweekly docetaxel in PROSTY were fatigue (89%), anemia (86%), pain (70%), neutropenia (60%), watery eyes (53%) and raised alkaline phosphatase concentration (50%); most common grade 3/4 AEs included neutropenia (36%), fatigue (15%), leucopenia (13%), infection (11%), and infection with neutropenia (6%). In our case series, anemia, lymphopenia, and neutropenia were the most common AEs.…”
Section: Discussionmentioning
confidence: 99%